THE INFLUENCE OF SALES PROMOTION, LOCATION AND SERVICE QUALITY ON PURCHASE DECISIONS FOR KAUMAN HOUSING, DEMAK DISTRIC - Farisa Dwi Setiawati; Rustono Rustono; Isnaini Nurkhayati; Jati Nugroho (Politeknik Negeri Semarang, 2023)
This study aims to understand the impact of sales promotion, location and service quality on purchasing decisions at Kauman Regency Housing Demak. To accomplish the stated goal, it is necessary to monitor the 70 respondents who have purchased a home in Kauman Regency Housing Demak. The methods of collecting data are interviews, questionnaires, and literature review with saturated samples. Data processing in this study uses SPSS programs Version 26. The data analysis is using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, partial t-test, F test, and coefficient of determination test. The results of the study have a positive and significant effect both partially and significantly on purchasing decisions. The results of the coefficient of determination (Adjusted R Square) of 0.598 means that sales promotion, location, and sales quality affect purchasing decisions by 59.8%, and the remaining 40.2% is influenced by other variables not examined in this study.